Is Pitch Height or Pitch Contour a Challenge? Production of Mandarin Tones in Hani-Mandarin Bilingual Children. - Aliang Li (Journal of Speech, Language & Hearing Research, 2025)
Purpose: The study aimed to determine the relative difficulty of Mandarin tone production in a classroom setting for native Hani-speaking children and to explore whether these bilingual children's tone production follows the same patterns observed in Mandarin monolingual children. Method: This study investigates Mandarin tone production in Hani-Mandarin bilinguals (n = 30) compared to Mandarin monolinguals (n = 20) using Growth Curve Modeling to analyze differences in pitch height and pitch contour between second language (L2) and first language (L1) Mandarin children. Results: Hani-Mandarin bilinguals produce Mandarin tones with distinct acoustic patterns compared to monolinguals: Hani-Mandarin bilingual children's Tone (T)1 and T4 differ from Mandarin monolingual children in pitch height, while T2 and T3 differ from Mandarin children in pitch contour. Hani-Mandarin bilinguals occasionally pronounce T3 as T2 or vice versa, displaying a bidirectional confusion between T2 and T3. Conclusions: L1 experience significantly influences L2 tone production. Bilingual children with a tonal L1 produce tones with higher static pitch targets similar to monolingual children, regardless of the differences between the L1 and L2 tonal systems. Complex pitch contours and laryngeal muscle activation patterns in L2 tones may hinder tone acquisition for both bilingual and even nativespeaking children.